Style Features in Communication of the Crews With Mission Control - Yusupova, Anna; Shved, Dmitry; Gushin, Vadim; Chekalina, Angelina; Supolkina, Natalia (Frontiers in Neuroergonomics, 2021)
In “Content,” an International Space Station (ISS) Russian segment space experiment, features of communication between the cosmonauts and the Mission Control Center (MCC) were studied using content analysis. The method is based on the concept of stress copings by Lazarus and Folkman. Differences found in the communication of cosmonauts led to assumptions about the existence of individual communication styles in routine communication between the cosmonauts and the MCC. The differences found were defined using V. Satir's classical model of communication types. The pre-dominance of three main communication styles (“computing,” “blaming,” and “placating,” as per Satir) was found. Manifestations and features of styles are discussed, considering the effectiveness of the “computing” style for ISS-MCC communication. Cosmonauts with a pre-dominance of this communication style, mostly are stable and with good self-control. An increase of the “blaming” and the “placating” style features in the communication of cosmonauts may require adaptation of the MCC communication and additional psychological support for the cosmonauts.